Silicon Dioxide Nanowires: Silica Nanowire Growth on Coscinodiscus Species Diatom Frustules via Vapor–Liquid–Solid Process (Small 47/2018). Issue 47 (26th November 2018) - Li, Aobo; Zhao, Xiaoguang; Anderson, Stephan; Zhang, Xin
Abstract : In article number 1801822, Xin Zhang and co‐workers employ a vapor‐liquid‐solid method to incorporate silicon dioxide nanowires on frustules, the exoskeleton structures from diatoms. This process features preferential nanowire growth on frustules, which is thermodynamically analyzed. Compared to the original frustule structures, the frustule‐nanowire composite material's surface area increases over 3‐fold, and the light scattering ability increases by 10%.